Implementation of Emotional Intelligence-Based Leadership in Improving the Performance of Community Learning Center (PKBM) Managers in Bandung City - Sriwardani; Tri Juniarti, Atty; Affandi , Azhar; Indriani Pratami , Eggi (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2026)
Leadership based intelligence emotional be one of factor crucial in determine success organization , no only in formal institutions , but also in non-formal institutions such as Activity Centers Community Learning (PKBM). Research This aim This study aims to analyze the implementation of emotional intelligence-based leadership and its impact on the performance of PKBM managers in Bandung City, focusing on PKBM Bina Cipta Ujungberung and PKBM Sukamulya. This study uses a qualitative descriptive approach through observation, interviews, and institutional document analysis. The results show that both PKBM have relatively good performance in terms of program quantity and quality, but still face obstacles in the effectiveness of resource use and managerial emotional management. Dimensions of emotional intelligence such as self-awareness, self-management, social awareness, and relationship management have not been optimally implemented. The implications of this study indicate that strengthening emotional competence in PKBM leaders contributes significantly to improving institutional performance. Therefore, emotional intelligence-based leadership training is needed to strengthen the managerial capacity of PKBM managers in facing the challenges of public education in the modern era.